Back to the Past: Segmentation with Infinite and Non-Volatile Memory - Laux Jr, Lauri; Hexsel, Roberto (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2016: Anais do XVII Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad.2016.14244, 2016)
The design of the current desktop/server operating systems is premised on the use of slow magnetic disks. Two recent developments, (i) RAM capacity nearing 264 bytes, and (ii) the introduction of non-volatile memory (NVRAM), provide an opportunity for a complete re-design of traditional Unix-like operating systems. We discuss some of the issues which support that proposition and oﬀer a few suggestions for areas that may beneﬁt from looking back at pioneering work. We then propose a segmented memory model for the MIPS processor.